Implementasi Teknologi Cerdas Berbasis IoT dan Telegram untuk Monitoring Kesehatan Jantung - Lintang Desy Pangesti; Arif Setia Sandi A; Rian Ardianto (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
The human heart acts as a vital organ that pumps blood throughout the body, and heart disease is the leading cause of death globally, including in Indonesia. To address this issue, this research proposes an Internet of Things (IoT)-based health monitoring system that can measure heart rate, oxygen saturation, and body temperature using MAX30100 and LM35 sensors. The system is equipped with real-time notification via Telegram and data display on an OLED screen. The method used is prototyping, with testing of sensor accuracy compared to conventional measuring instruments. The test results show good accuracy in BPM and SpO₂ measurements with an error of 5.78% and 3.6%, respectively, compared to the oximeter. However, body temperature measurement using the LM35 sensor showed an average error of 7.78%, due to the sensitivity of the sensor to ambient temperature.